English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2x - y + 3z = 2
3x + 2y - 4z = 5
x - 4y + z = -10

2007-09-09 09:19:15 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

8x - 4y + 12z = 8
9x + 6y - 12z = 15----ADD

17x + 2y = 23

3x + 2y - 4z = 5
4x - 16y + 4z = - 40------ADD

7x - 14y = - 35

17x + 2y = 23
7x - 14y = - 35

119x + 14y = 161
7x - 14y = - 35------ADD
126 x = 126
x = 1

17 + 2y = 23
2y = 6
y = 3

1 - 12 + z = - 10
z = 1

x = 1, y = 3 , z = 1

2007-09-13 07:50:19 · answer #1 · answered by Como 7 · 0 0

Multiply the first guy by two and add it to the second guy

7x + 2z = 9

Multiply the second guy by two and add it to the third guy

7x -7z = 0

Subtract these two.

9z = 9 or z = 1

Plug this value back in to the first two guys

2x - y + 3 = 2 or 2x - y = -1
3x + 2y - 4 = 5 or 3x + 2y = 9

Multiply the first guy by two and add it to the second guy

7x = 7 or x = 1

From this, we know that y = 3

Whew!

2007-09-09 16:38:12 · answer #2 · answered by PMP 5 · 0 0

If you multiply the second equation by 2 and add to the third equation, then this gives you:

7x-7z = 0,

which implies that x=z.

Use this result to solve any two equations by substitution to get:

x=z=1 and y=3.

2007-09-09 16:44:41 · answer #3 · answered by best-doctor 2 · 0 0

x = 1
y = 3
z = 1

2007-09-09 16:52:49 · answer #4 · answered by mathman 1 · 0 0

fedest.com, questions and answers